Determination of bound acrylonitrile content in nitrile rubber by pyrolysis-agas chromatography/mass spectrometry - QIN Peng, GENG Zhan-jie, FAN Guo-ning, WANG Fang, HU Hai-hua, WANG Chun-long, ZHAO Hong-guo (Hecheng xiangjiao gongye, 2023)
The bound acrylonitrile content in nitrile rubber (NBR) was determined by pyrolysis-gas chromatography/mass spectrometry, and the effects of furnace temperature and sample amount on pyrolysis were investigated. The butadiene and acrylonitrile fragments were identified by mass spectrometry, and the relationship between peak height ratio of acrylonitrile to butadiene and content ratio of acrylonitrile to butadiene was also established. Furthermore, the test results were compared with those determined by Kjeldahl method. The experiment results showed that the butadiene and acrylonitrile fragments in NBR had good chromatographic peak shape and recognition under the conditions of pyrolysis temperature of 600 ℃ and sample mass of 0.3-0.6 mg. The peak height of acrylonitrile with extracted ion M/Z 53 was positively correlated with the content of bound acrylonitrile in NBR, and the linear correlation coefficient of quantitative curve was above 0.99. Compared with Kjeldahl method, the absolute deviation of this method for determination of bound acrylonitrile content was not more than 0.7%.